1997
DOI: 10.1046/j.1365-3024.1997.d01-182.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactive cellular immune response to circumsporozoite proteins of Plasmodium vivax and P. falciparum in malaria‐exposed individuals

Abstract: Acquired immunity against the recombinant circumsporozoite protein of P. falciparum (rPfCS) or P. vivax (rPvCS) was studied in two malarious areas of the Brazilian Amazon. Cellular responsiveness, evaluated by proliferative assays, was detected in about 45% of individuals who had recovered from recent acute malaria infections. Peripheral blood mononuclear cells of individuals whose last malaria infection was by P. vivax responded more to the rCS proteins than those who had P. falciparum. Since in P. vivax infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…These data are consistent with our earlier studies that demonstrated that 30% of the individuals studied in the Brazilian Amazon had positive in vitro cellular responses to rPfCS. 18 The only other report concerning cellular responses to MSP-1 among Brazilians was to P.vivax. 28 The investigators used polypeptides representing the N-and C-terminal regions of the protein and showed PBMC stimulation ranging from 17% to 47% in the malaria-exposed group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with our earlier studies that demonstrated that 30% of the individuals studied in the Brazilian Amazon had positive in vitro cellular responses to rPfCS. 18 The only other report concerning cellular responses to MSP-1 among Brazilians was to P.vivax. 28 The investigators used polypeptides representing the N-and C-terminal regions of the protein and showed PBMC stimulation ranging from 17% to 47% in the malaria-exposed group.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) were isolated by Histopaque-1077 (Sigma) density gradient centrifugation as described elsewhere. 18 The PBMC were cultured in 96-well plates at a concentration of 1 ϫ 10 7 cells/ml in culture medium consisting of RPMI 1640 medium supplemented with 25 mM sodium bicarbonate, 25mM HEPES buffer, 3mM L-glutamine, 3% antibiotic-antimycotic mixture (300 U of penicillin, 300 g of streptomycin, 0.75 g of fungizone/ml), and 10% AB ؉ normal human serum. The recombinant proteins (rPfCS and rPfMSP-1) and yeast extract (control) were used at final concentrations of 10 g/ml;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 This may in part be due to immunologically cross-reactive epitopes between P. falciparum and P. vivax. 4 However, there was no negative correlation for the P. falciparum-P. malariae, 3 and longitudinal studies indicate that malarial parasites can also favourably affect the host environment for other species. 5,6 Summarizing the literature available in 1988, Richie 1 argued that suppression of one species by another could be a result of competition for nutrients or for host cells, or of an immune-mediated ceiling to parasite density.…”
Section: Introductionmentioning
confidence: 97%
“…7 Parallel tests of cellular responsiveness to P. falciparum and P. vivax recombinant CS (rCS) proteins, performed in areas where both parasites are transmitted, showed an overall positive rate of 45% in subjects recovering from acute malaria infection. 8 Although approximately half the people exposed to malaria in areas where transmission is low and unstable have T cells that recognize CS epitopes, these previous studies focused on subjects exposed for short periods of time, ranging from a few months to a few years. The mass migration of settlers to gold-rich areas or governmental agricultural settlement projects in the Amazon during the 1970s 9 meant that distinct groups are now exposed to malaria over decades.…”
Section: Introductionmentioning
confidence: 99%